(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the effectiveness of cryotherapy in the treatment of cancer. Methodology: this is a review study that analyzed articles from the last 05 years in Pubmed, Up to Date and Cochrane databases through active bibliographic research. Results: 09 studies were selected, including clinical trials and systematic reviews. Cryotherapy was compared to other methods as primary treatment and in association with other techniques, in the management of malignant and pre-malignant lesions. Equivalence was observed in efficacy when compared to other first-line methods, as well as similar rates of recurrence and adverse effects. However, cryotherapy was associated with inferior esthetic results. When in association, longer survival time was demonstrated in some studies, but higher recurrence rates in others. In the approach of pre-malignant lesions, the results were similar to the previous ones. Conclusion: despite its great potential in the treatment of cancer, cryotherapy still lacks greater evidence of its use in clinical practice, requiring more well-structured studies.